KELAYAKAN E-MODUL BERBASIS TPACK UNTUK MELATIH KEMAMPUAN LITERASI SAINS CALON GURU BIOLOGI - Sri Cacik; Tabitha Sri Hartati Wulandari; Christina Innocenti Tumiar Panggabean; Ifa Seftia Rakhma Widiyanti (Jurnal Inovasi Pendidikan dan Sains, 2022)
This study aimed to describe the feasibility of e-modules based on TPACK (Technological Pedagogical And Content Knowledge) to train the scientific literacy skills of Biology teacher candidates. This article is part of the research and development that has been done, namely developing e-modules based on TPACK, in which undergraduate students in Biology Education, FKIP, PGRI Ronggolawe University, Tuban, are the research subjects. Research and development are carried out using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). At the Development stage, the researcher validated three experts; material, language, and media experts. The instrument used at this stage is a validation sheet which contains several assessment indicators and supporting questions. The validation sheet given to material and media experts has 16 assessment indicators and three supporting questions, validation sheet given to linguists contains ten assessment indicators and three supporting questions. Based on the validation results, it has known that material, language, and media experts each assess 91.25%, 94%, and 93.7% then those were in the very good category. Material experts recommend that the e-module must add a link for enrichment material. Linguists give suggestions so that the sentences used are more communicative. Advice from media experts is to reduce the red color in TPACK-based e-modules. The conclusion obtained from the results of the validator's assessment is that the TPACK-based e-module is appropriate for use to train the scientific literacy skills of Biology teacher candidates.